REFORMASI, TEORI EKONOMI, DAN KEMISKINAN - Mubyarto Mubyarto (Journal of Indonesian Economy and Business (JIEB), 2004)
For 25 years now, the Pancasila economic theory has experienced “prosperity anddepression”. In 1980’s when the economy was booming the Indonesian economists weredebating seriously on the merit and demerit of the theory. Now after the economy had beenhaving difficulties to recover from the severe monetary crisis, the debate become hotterbecause the conventional economic theory has again demonstrated its inability. Inconnection with the role of IMF’s economists in helping Indonesian economists to rescuethe crisis, various national debate took place. The author’s brief meeting with MuhammadYunus, Bangladesh’s most prominent economist in Dacca reactivated our long timeconcern on the need of “native economic theory” for Indonesia which we had calledEkonomi Pancasila.Key words : self employment, socio-economic theory, poverty, ekonomi rakyat